Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1186/1748-717x-9-150
|View full text |Cite
|
Sign up to set email alerts
|

Hafnium oxide nanoparticles: toward an in vitropredictive biological effect?

Abstract: BackgroundHafnium oxide, NBTXR3 nanoparticles were designed for high dose energy deposition within cancer cells when exposed to ionizing radiation. The purpose of this study was to assess the possibility of predicting in vitro the biological effect of NBTXR3 nanoparticles when exposed to ionizing radiation.MethodsCellular uptake of NBTXR3 nanoparticles was assessed in a panel of human cancer cell lines (radioresistant and radiosensitive) by transmission electron microscopy. The radioenhancement of NBTXR3 nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
98
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 20 publications
6
98
0
Order By: Relevance
“…Developed by Nanobiotix, NBTXR3 is a novel radio enhancer utilizing a high electron density metal oxide (hafnium oxide) nanoparticle to increase radiotherapy efficacy without increasing the surrounding tissue dose (76). Incorporation of a high electron density material maximizes x-ray interactions producing a larger number of excited electrons and in turn forming more reactive radical species (77).…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…Developed by Nanobiotix, NBTXR3 is a novel radio enhancer utilizing a high electron density metal oxide (hafnium oxide) nanoparticle to increase radiotherapy efficacy without increasing the surrounding tissue dose (76). Incorporation of a high electron density material maximizes x-ray interactions producing a larger number of excited electrons and in turn forming more reactive radical species (77).…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…The negative surface charge of NBTXR3 NPs provides them with stability in aqueous solutions with pH ranging from 6 to 8. 53 The cellular uptake of the NBTXR3 NPs has been studied for a variety of cell lines, including epithelial, mesenchymal, and glioblastoma human cancer cells. It was observed that the NPs were taken by the …”
Section: Gold-based Nanoparticlesmentioning
confidence: 99%
“…51,52 Hafnium-based nanoparticles Nanoparticles with high electron density allow the deposit of large amounts of energy within living cells when activated by ionizing radiation. 53 In particular, surface-modified negatively charged NPs made of hafnium oxide ("NBTXR3," see Table 2) are currently being explored as selective radio enhancers for the local treatment of solid tumors. 53,54 Upon activation with ionizing radiation, these electron-dense particles generate large quantities of reactive oxygen species inside the tumor, which in turn are ultimately responsible for the cellular damage.…”
Section: Gold-based Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, only a few nanoparticle (NP)-radiation therapy combinations are undergoing clinical trials (only 3 records concerning NBTXR3 devices in ClinicalTrials.gov). 5 In order to speed up the preclinical development of radiation therapy enhancing NPs, numerous studies have tried to predict their in vitro or in vivo radiosensitizing effect. [6][7][8][9] The most common method, inherited from the practices of physics, is to use Monte Carlo simulators of particle transport in matter such as BEAM, MCNP, PENELOPE or Geant4.…”
Section: Introductionmentioning
confidence: 99%